Pengaruh Etos Kerja Islam dan Gaya Kepemimpinan Terhadap Kinerja Guru MTS Melalui Variabel Motivasi - Iid Pua Wadjo; Dwi Cahyono; Arik Susbiyani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine directly or indirectly the influence of the Islamic work ethic and leadership style on the performance of MTs teachers through motivational variables, a case study of MTs teachers in NTT. This research uses descriptive and quantitative research methods. The study population was all MTs teachers in NTT, totaling 1,324 teachers. The sample used was 133 teachers using a purposive sampling technique. The analysis technique used is the Structural Equation Model (SEM) using WarpPLS 7.0. The results of data analysis show that; Islamic work ethic has a significant effect on motivation; Islamic work ethic has a significant impact on performance; leadership style has a significant effect on motivation; leadership style has a significant effect on performance; motivation has a significant effect on motivation; Islamic work ethic has a significant effect on performance through motivation; leadership style influences performance through motivation. In conclusion, there is an influence of Islamic work ethic and leadership style on the performance of MTs teachers through motivational variables keyword : Islamic work ethic, leadership style, performance, motivation.